Salesforce for beginners : a step-by-step guide to optimize sales and marketing and automate business processes with the Salesforce platform - Shaalan, Sharif; Royer, Timothy (Expert insight., 2022)
Salesforce is the world's leading Customer Relationship Management (CRM) software, helping businesses connect with their constituents and partners. This book will give you a comprehensive introduction to managing sales, marketing, customer relationships, and overall administration for your organization. You'll learn how to configure and use Salesforce for maximum efficiency and return on investment. This book will teach you how to create activities, manage leads, manage users, set up security, customize your UX, work with third-party applications, build flows, develop your prospects and sales pipeline using opportunities and accounts, understand how you can enhance marketing activities using campaigns and much more. Packed with real-world business use cases, this Salesforce book will show you how to analyze your business information accurately to make productive decisions for your business. As you advance, you'll learn how to build various reports and dashboards in Salesforce to derive valuable business insights. Finally, you'll explore tools such as Salesforce Flows, approval processes, and assignment rules to achieve business process automation and set out on the path to becoming a successful Salesforce administrator. By the end of the book, you will know how to manipulate Salesforce to achieve your business goals.